O direito de ser diferente: uma análise do direito à educação inclusiva das pessoas com deficiência - MAURO, Fádia Yasmin Costa (Universidade Federal do Pará, 2019)
The present research defends the right to be different in the school, analyzing the perspective of the inclusive education of people with disabilities, to answer the question about which is best way to realize it within the society in order to promote the ideals of distributive justice that guarantee on equal terms the right to education of individuals with disabilities. To respond this question, this study is divided into three chapters. It first defines key elements such as who is disabled, social phenomena that leads to discrimination, among other fundamental definitions in order to answer who is the addressee of the right and why is important the recognition of difference. In the second chapter, it discusses what is inclusive education and how it is carried out, promoting a critical analysis of the main institutes that implicate in the understanding of the theme. Finally, this study makes a defense of the right to school inclusion, using political philosophy, from the theory of "justice as fairness" in Rawls as the one that best fulfills the idea of equality in the granting of rights and satisfies the premise of inclusive education for people with disabilities, and is complemented by Nussbaum's reading of human capacities, allowing the school development of these students and, therefore, considering these individuals from their singularities for the ensure of an effectively fair, human dignity and respect for difference. It is a study that aims to discuss the best way to promote access to inclusive education for people with disabilities, so that they receive qualitative teaching and capable of stimulating their abilities, from the perspective of international and national laws and theories of justice. The methodology adopted is eminently theoretical-doctrinal, using a regional and national bibliographic survey and also the philosophical references adopted in the present research, with the purpose of carrying out an interdisciplinary scientific study capable of contributing to the evolution of human rights, particularly to deficiency.